A Systematic Review of the Processes Underlying the Main and the Buffering Effect of Social Support on the Experience of Pain. Issue 11 (November 2018) - Che, Xianwei; Cash, Robin; Ng, Sin Ki; Fitzgerald, Paul; Fitzgibbon, Bernadette M.
Abstract : Objective: This review aimed to explore the processes that underlie the main and the buffering effect of social support on decreased pain experience. Materials and Methods: The systematic review was conducted according to the PRISMA guidelines. Online databases of PubMed and PsycINFO were searched for peer-reviewed articles using keywords ("social support, " OR "interpersonal, " OR "social presence, " OR "spouse, " OR "couple, " OR "marriage") AND "pain"). Articles were included if they examined the cognitive or behavioral processes linking social support to any aspects of reduced pain experience. Results: The database search identified 38 studies, of which 33 were cognitive-behavioral studies and 5 were neurobiological. Cognitive-behavioral studies generated a total of 57 findings of the analgesic influence of social support. This effect was further categorized as social support decreasing the adverse influence of pain-related stress (28/44 findings), reappraising pain-related stress (7/9 findings), and facilitating coping attempts (2/4 findings). Of the 5 neurobiological studies, the influence of social support on pain reduction was associated with reduced neural and physiological stress systems in response to painful stimuli. Discussion: This review presents evidence that the stress-buffering effect is more often able to account for the relationship between social support and pain experience. Moreover, findings suggest the critical significance of stress appraisal and attenuated stress systems in linking social support to aspects of reduced pain experience. Findings implicate the role of integrating perceived support and intimacy in support-oriented interventional trials for chronic pain. Abstract : Supplemental Digital Content is available in the text.